New concept of traction force applied to biliary self-expandable metallic stents - Hori, Yasuki; Hayashi, Kazuki; Yoshida, Michihiro; Naitoh, Itaru; Nakazawa, Takahiro; Miyabe, Katsuyuki; Shimizu, Shuya; Kondo, Hiromu; Nishi, Yuji; Umemura, Shuichiro; Kato, Akihisa; Ohara, Hirotaka; Joh, Takashi (Endoscopy, 2016)
Background and study aims: Various mechanical properties of self-expandable metallic stents (SEMSs) have been reported. They can be classified into the device behavior during and after deployment. While there have been several reports on the latter, information on the former is insufficient. During deployment, the position is maintained by retracting the delivery catheter. We propose that this pulling force be called the traction force and that the magnitude of traction force is termed the traction momentum. The aim of this study was to measure these parameters in order to clarify the properties of SEMSs in terms of their deployment.Material and methods: The traction force, traction momentum, and shortening rate of 10 different SEMSs were measured. Traction force was measured using in-house equipment, and the shortening rate was determined by measuring the stents.Results: The shortening rate was closely related to the stent structure. The traction force varied between 1.5 N and 9.4 N, and the traction momentum was significantly elevated in covered and braided stents. A high traction force did not imply a high traction momentum.Conclusions: A low or constant traction force and a minimal shortening rate significantly facilitated SEMS deployment to optimal positions. Traction force could be an important element for new ideal SEMS design.